Impact of plug-in hybrid electric vehicles on power system with high wind power penetration - Mahmoud Essam Harby; Said Elsayed Elmasry; Adel Elsamahy; Luis Marroyo; Javier Marcos (IAES International Journal of Robotics and Automation (IJRA), 2019)
The rising energy independence and environmental concerns are key drivers in the growing popularity of plug-in hybrid electric vehicles (PHEVs). Because of the intermittent nature of the renewable energy sources, this may cause a high-frequency oscillation of the power system. From another aspect, all the PHEVs have in common the batteries, which provide the storage capability that can be effectively harnessed when the vehicles are integrated into the grid. Such a storage capability can effectively integrate wind power into the grid and all indicators signalize that the PHEVs are the most promising technology of the future transportation system. In this paper, different case studies are applied on one area power system to show the effect of the high wind energy penetration on the power system frequency and how the PHEVs can play an effective role in mitigating the power system frequency oscillation and supporting the more penetration of the wind energy into smarter electrical grids. In addition, an advanced controller has been designed to improve the frequency response and to compensate the delay of the system. The designed controller is a genetic algorithm (GA) based PID (proportional-integral-derivative) controller, it has been proposed for tuning optimized PID parameters. The results show that the controller has played an effective role in decreasing the response overshoot and settling time when used with the PHEVs. The used variable load, the thermal power plant parameters, and the wind turbine parameters are the same for the five case studies.